Transformatif Leadership of School Principles in Improving the Quality of Education Management - Zainal Muttaqin; Adang Hambali; Nurwadjah Ahmad Eq; Asep Nursobah (UIN Sunan Gunung Djati Bandung, 2021)
This study focuses on the transformatif leadership of school principals in improving the quality of education management. By using qualitative methods and a literature study approach, this study concludes that the principal's transformatif leadership in improving the quality of education management needs to pay attention to the principal's learning competency criteria. In addition, school principals also need to pay attention to various dimensions of transformational leadership and the existing concept of quality improvement. It is intended that the principal's transformatif leadership will ultimately be able to improve the quality of educational institutions. Thus, the principal's transformatif leadership in improving the quality of education can be achieved optimally, so as to be able to create quality educational institutions.